Losing less and winning more: project strategies to negotiate between conservation and development in the Lower Mekong - Preece, L.; Herrero Cangas, B.; Sunderland, Terry C.H.; Achdiawan, R.; Ruíz Pérez, M.; Campbell, Bruce M.; Stacey, Natasha (2009)
Conservation organisations are faced with the complexities between protecting forests, developing local livelihoods and strengthening institutions. The aim of this paper is to analyse the strategies employed by organisations to implement conservation and development, and to assess how project progress is improved by project operations. This paper analyses 42 projects working in 15 conserved forest sites in Laos, Cambodia and Vietnam. We use multivariate techniques on a large set of variables to explore patterns between sites, project activities and management. The major threats to biodiversity in the Lower Mekong are hunting and logging. Primary site-level conservation projects focus significantly on law enforcement, but also use developmental and institutional building tools to reduce pressure on conserved areas and improve both conservation and development outcomes. Although achieving the combined goals of conservation and development is necessary in most situations, trade-offs, however, these two goals are common and integrated approaches can sometimes compromise both conservation and development outcomes. Many organisations collaborate with government and non-government organisations and use participatory and consultative approaches with local people to achieve their objectives. We conclude that while integrating conservation and development is often necessary, trade-offs must be acknowledged because they influence project outcomes. Partnerships and consultation with multiple interest groups can greatly improve the effectiveness of project implementation.